Exploring spatial justice in times of disruptions: Introduction to the special issue - Lena Greinke; Peter Schmitt; Rainer Danielzyk (European Journal of Spatial Development)
The concept of spatial justice encompasses a number of diverse theoretical, political and normative issues. It sheds light on the way  resources are allocated across different types of territories and how spatial patterns influence, enhance or confine people’s opportunities. As such, the concept of spatial justice prompts a rethink of many of the substantial challenges of urban and regional development, which explains its topicality amongst policymakers and academics alike. The ARL International Summer School 2022 has thus invited doctoral students and other early career researchers to Stockholm  University to debate conceptual, methodological and empirical aspects under the theme ‘Exploring spatial justice in times of disruptions’. The articles in this special issue underscore the importance of the quest to understand this multifaceted concept from  different perspectives.